KARAKTERISASI DAN SIFAT KEMAGNETAN PASIR BESI EKSTRAKSI ASAL PANTAI BETAF SARMI, PAPUA - Haryati, Endang; Dahlan, Khaerian; Wirman, Shabri Putra (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2019)
Characterization and magnetic behavior test of extracted iron sand from Betaf beach of Sarmi Papua was studied. The purpose of the recearch was to determine minerals content, phase of iron compound, and magnetic behavior of extracted iron sand from Betaf beach of Sarmi Papua were caculate using XRF, XRD and VSM. The result showed that extrated iron sand was contained 43,81% of Iron (Fe), 25,75% of Silika (Si) and 30,44 % others. The XRD pattern showed that the highest peak was magnetite (Fe3O4) at 2= 35,65o.  The histerisis curve of VSM showed that extracted iron sand from Betaf beach of Sarmi Papua was superparamagnetic material where maximum saturation magnetization (Ms) value of 4,54 emu/gr, remanen magnetization (Mr) value of 0,371 emu/gr and coercivity field (Hc) value of 208 Oe.